1997
DOI: 10.3109/10715769709065769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Active Oxygen Radicals on Protein and Carbohydrate Moieties of Recombinant Human Erythropoietin

Abstract: Our previous study showed that active oxygen radicals generated from a Fenton system and a xanthine plus xanthine oxidase system caused serious loss of in vivo bioactivity of recombinant human erythropoietin (EPO), a highly glycosylated protein. In the present study, we characterized the oxidative modifications to the protein and carbohydrate moiety of EPO, which lead to a reduction of its bioactivity. In vitro bioactivity was reduced when EPO was treated with oxygen radicals generated from a Fenton system in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 32 publications
1
36
0
2
Order By: Relevance
“…This result is in line with the lower heme levels in b-thalassemic late erythropoiesis than in normal late erythropoiesis. In addition we treated the control cells with 16 μM H2O2, as previously reported by Uchida et al, 24 and found a marked reduction in ALAS-2 activity and in heme content compared to the activity of normal controls at day 14 of culture (data not shown).…”
Section: D-aminolevulinate Synthase-2 Activity Is Reduced In B-thalassupporting
confidence: 54%
See 1 more Smart Citation
“…This result is in line with the lower heme levels in b-thalassemic late erythropoiesis than in normal late erythropoiesis. In addition we treated the control cells with 16 μM H2O2, as previously reported by Uchida et al, 24 and found a marked reduction in ALAS-2 activity and in heme content compared to the activity of normal controls at day 14 of culture (data not shown).…”
Section: D-aminolevulinate Synthase-2 Activity Is Reduced In B-thalassupporting
confidence: 54%
“…24 Details on cytoflourimetric analysis are reporetd in the Online Supplementary Design and Methods. Whenever indicated, PRDX2 was immunoprecipitated from cell lysates (11¥10 6 cells).…”
Section: Peroxiredoxin-2: Cytofluorimetric and Immunoprecipitation Assaymentioning
confidence: 99%
“…The glycosylated chains confer some of the biological activity to the EPO molecule, which is stabilized by the carbohydrate chains. The oligosaccharides in EPO may protect the protein structure from oxygen radical destruction (Uchida et al, 1997). In addition, the N-and O-linked chains may be necessary for the cellular secretion of EPO (Krantz, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The glycosylated chains are important for the biological activity of EPO and can protect EPO from oxygen radical degradation. The carbohydrate chains stabilize EPO (Toyoda, et al, 2000) and the oligosaccharides in EPO may protect the protein from oxygen radical activity (Uchida, et al, 1997). The N-glycosylated chains are believed to contribute to the thermal stability of EPO (Tsuda, et al, 1988).…”
Section: Epo Expression Structure and Receptor Role In Cells And Timentioning
confidence: 99%